Kelimpahan dan Keanekaragaman Jenis Burung di Enclave Lindu Taman Nasional Lore Lindu - Heru Setiawan (Universitas Atma Jaya Yogyakarta, 2013)
AbstractLindu Enclave area is an area that cannot be separated from the Lore Lindu National Park (TNLL) because it is situated in the TNLL area. Lore Lindu National Park is located in the Wallacea area with high level diversity especially for the bird diversity. The existence of TNLL has an important role as habitat for 80% of Sulawesi endemic birds. This study aimed to determine the diversity of birds in the Lindu Enclave. Data was collected using PIA (Point Index of Abundance) method with 14 observation points which were scattered in two villages: Tomado Village and Anca Village. The results of bird watching analysis showed that as many as 51 species of birds from 25 families were found in the Lindu Enclave. Out of 51 birds, there were 14 species categorized in the protected birds and 15 species were endemic birds. Out of 15 species endemic bird, 4 species were categorized in the protected bird species. The most common bird species was intermediate egret (Egretta intermedia), as many as 86 individuals. Bird diversity index in Lindu Enclave area was 3.23 that categorized on the high diversity level.Keywords: Lindu Enclave, biophysical, bird diversity, Lore Lindu National ParkAbstrakKawasan Enclave Lindu merupakan daerah yang tidak dapat dipisahkan dari Taman Nasional Lore Lindu (TNLL) karena letaknya yang berada di dalam kawasan TNLL. Taman Nasional Lore Lindu berada dalam kawasan Wallacea dengan tingkat keanekaragaman hayati yang tinggi khususnya jenis burung. Keberadaan TNLL mempunyai peranan yang penting sebagai habitat burung karena 80% burung endemik Sulawesi terdapat di kawasanÂ ini. Penelitian ini bertujuan mengetahui keanekaragaman jenis burung di kawasan Enclave Lindu. Pengambilan data menggunakan metode IPA (Indeks Point of Abundance) dengan 14 titik pengamatan yang tersebar di dua desa yaitu Desa Tomado dan Desa Anca. Hasil penelitian menunjukkan sebanyak 51 jenis burung dari 25 famili berhasil ditemukan di kawasan Enclave Lindu. Dari 51 jenis burung tersebut, terdapat 14 jenis yang termasuk dalam jenis burung dilindungi dan 15 jenis burung endemik. Dari 15 jenis burung endemik tersebut terdapat 4 jenis burung yang termasuk dalam jenis burung yang dilindungi. Jenis burung yang paling umum ditemukan adalah Kuntul perak (Egretta intermedia), sebanyak 86 individu. Indeks keanekaragaman jenis burung di kawasan Enclave Lindu adalah 3,23 dengan tingkat keanekaragaman yang tergolong tinggi.Kata kunci: Enclave Lindu, biofisik, keanekaragaman burung, Taman Nasional Lore Lindu